Effect of Fermentation Time for a Combination of Rice Straw and Tithonia (Tithonia diversifolia) on the NDF, ADF, and Cellulose Content as Ruminant Feeding - Muhajir, Abdul Latif; Astuti, Tri; Asri, Alfian (Journal of Animal Nutrition and Production Science, 2023)
This research aims to examine the effect of fermentation time for rice straw and tithonia (Tithonia diversifolia) on local microorganisms in the rumen of cows. This research was carried out using a Completely Randomized Design with four treatments and 4 replications. Treatments consisted of P0 (Combination of rice straw and tithonia without local microorganisms), P1 (Combination of rice straw and tithonia with 0 Day Incubation ), P2 (Combination of rice straw and tithonia with 7 Day Incubation ), and P3 (Combination of rice straw and tithonia with 14 Day Incubation. The variables measured are NDF, ADF, and Cellulose. The results of the analysis of variance showed that the effect of fermentation of rice straw and tithonia with local microorganisms in the rumen content had a very significant effect (P<0.01) on NDF, ADF, and Cellulose. Based on this research, it shows that the combination of rice straw and tithonia can increase the content of NDF, ADF, and Cellulose.